Il grande assente: il dialetto nella "Stori" di De Sanctis - Pietro Gibellini (Lea, 2017)
Italian literature includes a large number of dialect writers. Their number is particularly high in Quadrio’s History of Italian Literature, but was reduced in the works written in the Romantic Age (i.e. those by Ginguené, Corniani, Ugoni and Emiliani). The elimination of dialect writers was most drastic in the masterly History of Italian Literature by Francesco De Sanctis published in 1870 for use in schools. He ignored them basically for political reasons, being an ardent supporter of the unity of Italy. Thus he considered dialects an obstacle to this unity. For this reason he backdated the existence of a common Italian language to as early as the 13th century, using the term ‘dialect’ only for writings by Tuscan authors who made use of the spoken language of their region, which could easily be understood by all other Italians.